2011
DOI: 10.3390/molecules16053663
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Oral Acute Toxicity Studies of Lantana camara Leaf Extract

Abstract: Background: The objective of this study was to investigate the toxicity of Lantana camara methanol extract. Methods: In order to evaluate the toxicity of Lantana camara, the acute toxicity of the methanolic extract on adult mice and cytotoxicity test on Vero cell line were investigated. A fixed large dose of 2 g/kg body weight of L. camara leaf extract was administrated by a single oral gavage according to the OECD procedure. Results: In 2 weeks, L. camara leaf extract showed no obvious acute toxicity. While f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…However, female mice lost BW after being treated with a single dose of leaf extract in acute toxicity test, while, males lost organ mass, particularly for heart and kidney. The biochemical liver function tests showed significantly elevated TBIL and ALT in the L. camara leaf extract treated female mice group compared with the control group [76].…”
Section: Side Effects and Toxicitymentioning
confidence: 84%
See 1 more Smart Citation
“…However, female mice lost BW after being treated with a single dose of leaf extract in acute toxicity test, while, males lost organ mass, particularly for heart and kidney. The biochemical liver function tests showed significantly elevated TBIL and ALT in the L. camara leaf extract treated female mice group compared with the control group [76].…”
Section: Side Effects and Toxicitymentioning
confidence: 84%
“…The results showed that leaf extract at concentrations up to 500 µg/ml inhibited the growth of cells (2.5 times less than did Triton 100×1%). The cytotoxicity was declined when the concentrations of the extract were elevated [76].…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Ethanolic and aqueous extract of leaves of V. negundo shows antitumor effect against Dalton's Ascitic Lymphoma (DAL) in Swiss Albino mice [35]. Pour et al, (2011) reported that the methanolic extract of L. camara was studied for its cytotoxicity and oral acute toxicity [36]. Against Dalton's ascetic lymphoma, leukemia and many cancer cell lines, B. variegata stem was shown to have cytotoxic activity.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…[11] Thus, two doses (low and high), as recommended by Organisation for Economic Co-operation and Development [12] guidelines of 250 and 500mg/kg of compound was suspended in 10% Tween20 and administered by gavage to mice weighing between 25-30g (n=5). The control group received tween 20 alone.…”
Section: Treatmentmentioning
confidence: 99%